2019
DOI: 10.3389/fpls.2019.00026
|View full text |Cite
|
Sign up to set email alerts
|

NBS-Encoding Genes in Brassica napus Evolved Rapidly After Allopolyploidization and Co-localize With Known Disease Resistance Loci

Abstract: Genes containing nucleotide-binding sites (NBS) play an important role in pathogen resistance in plants. However, the evolutionary fate of NBS-encoding genes after formation of allotetraploid Brassica napus (AnAnCnCn, 2n = 38) is still unknown. We performed a genome-wide comparison of putatively functional NBS-encoding genes in B. napus and its progenitor species Brassica rapa (ArAr, 2n = 20) and Brassica oleracea (CoCo, 2n = 18), identifying 464, 202, and 146 putatively functional NBS-encoding genes respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 101 publications
1
44
1
Order By: Relevance
“…This was higher than the numbers reported by Chalhoub et al (2014) who identified 425, 211 and 274 NLR genes from B. napus B. rapa and B. oleracea respectively using the MAST approach, but with a more stringent E-value. Using HMMER and Pfam based on functional NLR coding domains as search queries and excluding pseudogenes, Fu et al (2019) found 464, 202 and 146 NLR genes respectively resulting in much fewer NLR genes than identified by Alamery et al (2018). Similarly using HMMER and Pfam approaches, Yu et al (2014) identified 206 NLRs from B. rapa and 157 from B. oleracea and Zhang et al (2016) identified 204 from B. rapa.…”
Section: Genome-wide Identification Of Nlr Genes In Brassica Speciesmentioning
confidence: 99%
“…This was higher than the numbers reported by Chalhoub et al (2014) who identified 425, 211 and 274 NLR genes from B. napus B. rapa and B. oleracea respectively using the MAST approach, but with a more stringent E-value. Using HMMER and Pfam based on functional NLR coding domains as search queries and excluding pseudogenes, Fu et al (2019) found 464, 202 and 146 NLR genes respectively resulting in much fewer NLR genes than identified by Alamery et al (2018). Similarly using HMMER and Pfam approaches, Yu et al (2014) identified 206 NLRs from B. rapa and 157 from B. oleracea and Zhang et al (2016) identified 204 from B. rapa.…”
Section: Genome-wide Identification Of Nlr Genes In Brassica Speciesmentioning
confidence: 99%
“…Expression analysis in eight tissues, a measurement of the activity and function of genes, showed that NBS genes were highly or preferentially expressed in the root (Fig. 5c), resulting from the greater pressure on the root than the other tissues 43 . Among these NBS genes, the tandem duplication did not show lower expression levels, which was inconsistent with the overall result.…”
Section: Tandem Gene Duplicationmentioning
confidence: 99%
“…Focusing on the NLR genes, comparative genomics and transcriptomics analyses supplemented with a database query on B. napus and its progenitors, B. rapa and B. oleracea, revealed many more NBS (also known as NLR) genes in the C sub-genome of B. napus. A number of these genes underly the QTL regions for resistance against Blackleg, Sclerotinia and Clubroot, supporting the concept that the diversification of the R genes likely happened after interspecific hybridisation between B. rapa and B. oleracea [ 90 ].…”
Section: Application Of Omics Technologies In Brassica mentioning
confidence: 72%
“…capitata ) [ 88 ] and the in silico exploration of 641 NBS-LRR-type disease resistance genes in B. napus , together highlighting the genomic distribution and structural variation of these genes in B. napus [ 89 ]. Other examples include the in silico evolutionary study of NBS genes in B. napus , where comparative genomic analysis highlighted the NBS gene’s distribution from its progenitors B. rapa and B. oleracea in relation to the three main Brassica diseases—Blackleg, Clubroot and Sclerotinia [ 90 ]. Coupled with modern bioinformatics tools and the integration of multi-omics data sets, in silico methods are powerful tools that rapidly provide accurate and detailed models to answer various research questions ranging from candidate gene identification to evolutionary pathways of resistance mechanisms in both the Brassica host and the fungal pathogens [ 91 ].…”
Section: Application Of Omics Technologies In Brassica mentioning
confidence: 99%